Gender Responsive Budgeting in Indonesia: Village Financial Budget Planning - Indah Ferina, Zahrah; Ganis Sukoharsono, Eko; Purwanti, Lilik; ., Roekhudin (KnE Social Sciences, 2023)
This study aimed to analyze how the budget of a village is gender-based based on Thinking Fatmawati. This study used a qualitative approach to critical ethnography (feminist). Data were collected through observation and in-depth interviews with village informants in Sitiarjo, Malang, East Java, Indonesia. Village Sitiarjo is an existing village that implements a gender-responsive budget. The results revealed concerns in the village regarding gender-oriented budget planning. Additionally, there are only a few programs that are gender oriented. However, implementing the gender-oriented budget is still in its initial stages. The planning process includes women’s participation in the village government’s deliberations. The planning process budget is expected to have Sprit Fatmawati, where women must be rational in making decisions for the economic and social good in the home or life around them while upholding religious and cultural values. This step is essential for the inclusiveness and sustainable development of the village. Keywords: Gender, Planning Budget Finance Village, Budget Gender Responsive